The subcutaneous ICD replacement in the clinical practice: preliminary observations from the multicentre RHYTHM DETECT. (19th May 2022) - Bianchi, V; Viani, S; De Filippo, P; Dello Russo, A; Checchi, L; Biffi, M; Caravati, F; Giammaria, M; Pisano', E; Papa, A; Francia, P; Bongiorni, M; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Experience with the subcutaneous implantable cardioverter‐defibrillator (S‐ICD) is expanding rapidly. However, few data on generator replacement exist. Purpose: The aim of this analysis was to describe the procedural characteristics of the pulse generator replacement in the current Italian practice and to provide a preliminary insight in the possible acute complications associated with first elective S-ICD generator replacements. Methods: We analyzed 106 consecutive patients enrolled in the Rhythm Detect registry who underwent elective replacement of the S-ICD generator from September 2019 to July 2021. Procedures were accomplished according to the local clinical practice. A chest X-ray was performed, and the PRAETORIAN score was assessed and compared with the one measured after the first implantation. Results: All replacements were performed in electrophysiology laboratories, 50% in day-hospital regimen, by 1 or 2 expert operators. Procedures were performed using local (87%) or general anaesthesia (13%). The median procedure duration was 40 (30-45) min. The previous S-ICD generator was in a subcutaneous pocket in 58 (55%) patients, and in an intermuscular pocket in the remaining patients. The PRAETORIAN score of the previous system was low (<90) in 93% of patients and intermediate in 7% of patients. In all patients with the device in an intermuscular pocket, the PRAETORIAN score was <90. During the replacement procedure, 22 S-ICD (3 with PRAETORIAN ≥90 before replacement) were removed from the initial subcutaneous position and placed in an intermuscular pocket. After replacement all patients with intermuscular devices had a score <90, and the overall proportion of patients with low-risk PRAETORIAN score raised to 97%. Defibrillation testing was performed only in 10% of patients, while testing was performed in 77% of patients at the first implantation procedure. No procedure-related complications occurred. Conclusions: S-ICD replacements seem easy to perform with no peri-procedural complications. The adoption of an intermuscular pocket is associated with optimal positioning according to the PREATORIAN score, and seems preferred also in many cases of generators previously placed subcutaneously. In the Italian clinical practice conversion testing is rarely performed at device replacement.